2021
DOI: 10.7759/cureus.13304
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ceramic-on-Ceramic and Ceramic-on-Highly-Crosslinked-Polyethylene in Primary Total Hip Arthroplasty: Findings of a Meta-Analysis

Abstract: Introduction An optimal hip implant is biocompatible, durable, and resistant to chemical and mechanical wear. This analysis aimed to compare failure (revision) and complication rates between ceramic-on-ceramic (CoC) and ceramic-on-highly-crosslinked-polyethylene (CoHXLPE) implants. Methods This review comprised of scientific literature published between 1995 and 2019. We included randomized controlled trials in adults (>18 years) that presented results of CoC and CoHXLPE total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Multiple studies have shown a decrease in the release of polyethylene particles in the cases of XLPE and HXLPE compared to the case of UHMWPE [ 78 ] ( Figure 2 A,B). Kuzyk et al, in a systematic review, highlighted a much greater penetration of the prosthetic head in UHMWPE [0.137 mm/year] compared to XLPE [0.042 mm/year] [ 140 ]. Wear rates for UHMWPE of 0.1–0.2 mm/year were reported with large particles, compared to the wear rate for HXLPE of 0.051–0.25 mm/year with small particles [ 140 ].…”
Section: The Choices Of the Bearing Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown a decrease in the release of polyethylene particles in the cases of XLPE and HXLPE compared to the case of UHMWPE [ 78 ] ( Figure 2 A,B). Kuzyk et al, in a systematic review, highlighted a much greater penetration of the prosthetic head in UHMWPE [0.137 mm/year] compared to XLPE [0.042 mm/year] [ 140 ]. Wear rates for UHMWPE of 0.1–0.2 mm/year were reported with large particles, compared to the wear rate for HXLPE of 0.051–0.25 mm/year with small particles [ 140 ].…”
Section: The Choices Of the Bearing Surfacesmentioning
confidence: 99%
“…Kuzyk et al, in a systematic review, highlighted a much greater penetration of the prosthetic head in UHMWPE [0.137 mm/year] compared to XLPE [0.042 mm/year] [ 140 ]. Wear rates for UHMWPE of 0.1–0.2 mm/year were reported with large particles, compared to the wear rate for HXLPE of 0.051–0.25 mm/year with small particles [ 140 ].…”
Section: The Choices Of the Bearing Surfacesmentioning
confidence: 99%